MENINGKATKAN PRESTASI PESERTA DIDIK MELALUI PENDIDIKAN FULL DAY SCHOOL - Tri Prasetyo Utomo (AL-ASASIYYA: Journal Of Basic Education, 2017)
Education can be done well if it gets the support of the elderly, the environment and the institutions that exist. The primary purpose of education is to develop potential religious, spiritual self-control, personality, intelligence, morals, as well as the necessary skills themselves, society, and nation and State as set forth in the national education goals. In order to realize these goals need strategies, methods, techniques and ways in the hopes of all potentials can be developed and optimize. Full day school education model into a system of learning that seeks to offer an alternative in realizing the purpose of education. The system is applied in a full day of instruction school stressing the aspects of development including the following character values, honest, religious tolerance, hard work, creative, independent, democratic, curiosity, passion, love of the fatherland, to appreciate the achievements, friendly/communicative, peace-loving, an avid reader, care for the environment, social responsibility and caring. The achievements of learners can be achieved by developing the institution of learning system using full day school, where students and teachers are active in learning activities and entwined deep emotional bond as well as control the influence from the environment outside the school who observed and controlled.